THREATS OF MARITIME TERRORISM IN INDIAN OCEAN : LESSONS LEARNT FROM GULF OF ADEN CASE STUDY - Muhammad Junaid Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
Maritime terrorism poses a significant threat in the Indian Ocean region (IOR), with Gulf of Aden amongst prominent hotbeds. The multifaceted challenges presented by maritime terrorism and various response options to address the growing security concerns have been evaluated within the larger context of Maritime Terrorism. The paper delves into the efforts made by littoral governments, blue water navies with regional cum international organizations to counter this menace of terrorism and undertake substantial safeguards. The importance of collaborative approach, collated intelligence sharing and due focus on capacity building measures needed to combat maritime threats in IOR have been recurrently talked about. Through an in-depth analysis of the “Gulf of Aden” as a case study, valuable insights for policymakers and stakeholders in formulating effective white-paper to strategize mitigation of posed risks in the region have been suggested. The paper unfolds arguments of the littoral nations of the region jostling in a geo-political struggle for power and economy. It concludes with regional strategic policy consultations inclusive of traditional and non-traditional maritime concerns, which can act as an impetus for betterment of inter-regional relations by offering safe Sea Lines of Communications (SLOCs).